Analisis Jaringan Wacana pada Pembentukan UUTPKS di Media Daring - Evvy Silalahi (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
This study aims to explore the construction of the TPKS Bill (Draft Law on the Elimination of Sexual Violence) into the TPKS Law (Act of Sexual Violence) through discourse debates in online mass media and the actors involved in the discourse battle. Many obstacles were faced related to the formulation of the material from the TPKS Bill. The theory used is the Advocacy Coalition Framework (ACF) with the discourse network analysis method. The unit of analysis is digital text from online mass media, the sample is 109 statements sourced from 26 news articles. The results of the study show that in the process of making the TPKS Law there was a coalition of parties that supported and opposed, generally more who supported the UUTPKS being ratified, while there were three political parties who opposed it.